2020
DOI: 10.14393/bj-v36n2a2020-43255
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and physiological quality of arabic coffee under different fermentation times

Abstract: The value of coffee presents a significant increase influenced by the improvement of the beans quality, so that a coffee made by beans with an inferior quality has a lower acceptance in the market and a reduction in therms of commercialization value. The different time of fermentation of the coffee in water can give rise to different beverage and physiological quality of its seeds, and may interfere in its commercialization value and in the production of seedlings in nurseries. The target of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…For the total score, the treatments associated with ME1 obtained an average value of 81.35 with a maximum of 83.92, and those associated with ME2 obtained an average value of 82.05 with a maximum of 83.83. The maximum values obtained coincide with the maximum value of 84 points reported by Do Carmo et al, 2020 [34], for the treatment of 18 h of fermentation. De Carvalho et al, 2018 [28], reported scores higher than 80 and obtained the highest scores in the sensory attributes of aroma, flavor, acidity, body, and balance in inoculated treatments compared to spontaneous fermentation, while sweetness, cleanliness, and uniformity were statistically similar for both treatments, possibly due to the absence of sensory defects.…”
Section: Sensory Qualitysupporting
confidence: 89%
See 1 more Smart Citation
“…For the total score, the treatments associated with ME1 obtained an average value of 81.35 with a maximum of 83.92, and those associated with ME2 obtained an average value of 82.05 with a maximum of 83.83. The maximum values obtained coincide with the maximum value of 84 points reported by Do Carmo et al, 2020 [34], for the treatment of 18 h of fermentation. De Carvalho et al, 2018 [28], reported scores higher than 80 and obtained the highest scores in the sensory attributes of aroma, flavor, acidity, body, and balance in inoculated treatments compared to spontaneous fermentation, while sweetness, cleanliness, and uniformity were statistically similar for both treatments, possibly due to the absence of sensory defects.…”
Section: Sensory Qualitysupporting
confidence: 89%
“…Treatments with the same process temperatures and prolongation times of the fermentation process in the stages of maturity EM1 and EM2 did not present defects with the same frequency as the treatment associated with EM3. Do Carmo et al, 2020 [34], evaluated 6, 12, 18, 24, 30, and 36 h of fermentation and found the lowest values of sensory score in treatments 30 and 36, reporting a green astringency associated with changes in the cell membranes of the grains, which determined that the excess fermentation was detrimental to the quality of the drink and the physiological quality.…”
Section: Sensory Qualitymentioning
confidence: 99%
“…Arabica coffee is one of the main agricultural products that are marketed worldwide and plays a key role in the economy of several countries, especially those that are the largest producers (Do Carmo et al, 2020;Pereira et al, 2020;Ribeiro et al, 2017). Brazil, one of the largest producers of Arabica coffee, is responsible for more than 40% of its global production (USDA, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Los nuevos procesos de beneficio del café, tales como la fermentación que, según (Martinez , Arístizabal, & Moreno, 2017) y (Carmo, Barbosa, Krause, & Peterle, 2020),se basa primordialmente en el reposo del grano durante tiempos determinados con el fin de que, al finalizar dicho proceso, obtenga mejores resultados en cuanto al puntaje en taza obtenido.…”
Section: Calidadunclassified